2017
DOI: 10.1108/ijqss-04-2016-0035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total quality management in local authorities

Abstract: Purpose The purpose of this study is to determine the main total quality management (TQM) factors adopted and the respective results achieved by local authorities – municipalities. Determining the degree to which TQM influences the respective results is also an aim of the present study. Design/methodology/approach A research study was designed to be carried out in Greek local authorities – municipalities, 125 of which were approached through interviews with chief executive officers (CEOs) based on a structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 90 publications
5
34
0
8
Order By: Relevance
“…La GCT implica la adopción por los gobiernos locales de un sistema de gestión global que construye una personalidad corporativa única y dinámica, basada en el compromiso de los empleados hacia la entrega de un valor constante a todos los grupos de interés, mediante la mejora continua del conjunto de procesos organizativos (Psomas et al, 2017).…”
Section: La Investigaciónunclassified
See 2 more Smart Citations
“…La GCT implica la adopción por los gobiernos locales de un sistema de gestión global que construye una personalidad corporativa única y dinámica, basada en el compromiso de los empleados hacia la entrega de un valor constante a todos los grupos de interés, mediante la mejora continua del conjunto de procesos organizativos (Psomas et al, 2017).…”
Section: La Investigaciónunclassified
“…Podemos, por tanto, establecer que la distribución de las ciudades en base a su adopción de la GCT y de la DEU es muy similar, demostrando la vinculación entre ambas y respondiendo a la tercera pregunta de investigación. Así, como se muestra conceptualmente, la DEU y la GCT están basadas en una profunda reflexión estratégica en las organizaciones y en la toma de decisiones coherentes que buscan la satisfacción de los diversos grupos de interés de manera continua (Psomas et al, 2017), y la generación de resultados competitivos. En los casos estudiados, se demuestra que la adopción del modelo EFQM ha generado mecanismos, conocimiento y experiencia suficientes como para sustentar el desarrollo de la DEU.…”
Section: Conclusionesunclassified
See 1 more Smart Citation
“…Reforms of public sector which is realized in individual countries have a goal a better performing public sector (Wynen, 2014). Public administration provides social justice and influences citizen's quality of life, and it is considered as a major factor of a country's economic development and growth (Psomas and Vouzas and Bouranta and Tasion, 2016). The process of managing of public institutions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that quality schemes in the public sector have been found to improve facility management, reducing cost, staff motivation, moral and satisfaction [3], citizen satisfaction and overall organizational performance [4]. Although there is considerable research material and knowledge concerning the adoption of TQM in manufacturing environment, relatively few TQM studies in the service sector, and more specifically in the public service sector [7]. Some literature has noted that there is still no approriate framework for applying TQM especially in the public sector [5], [6].…”
Section: Introductionmentioning
confidence: 99%